Semantic architectures and dashboard creation processes within the data and analytics framework. (16th June 2020) - Petito, Michele; Fallucchi, Francesca; Luca, Ernesto William De
The open data tools currently on the market do not exploit the semantic web, or provide tools for data analysis and visualisation. Most of them are simple open data portals that display a data catalogue, often not even fulfilling the lowest level of the famous five-star model. The Data and Analytics Framework (DAF), a project run by the Italian government, is enabled to extract knowledge from the immense amount of data owned by the State. It favours the spread of Linked Open Data thanks to the integration of the network of controlled ontologies and vocabularies (OntoPiA). The research outlined in this paper illustrates some of the platform's competitive solutions and introduces the five-step process to create a DAF dashboard, as well as the related data story. The case study created by the authors concerns tourism in Sardinia and represents one of the few demonstrations of a real case being tested in DAF.